2006
DOI: 10.1111/j.1440-1738.2006.00518.x
|View full text |Cite
|
Sign up to set email alerts
|

Oceanic plateau accretion inferred from Late Paleozoic greenstones in the Jurassic Tamba accretionary complex, southwest Japan

Abstract: The Jurassic Tamba accretionary complex is divided into two tectonostratigraphic suites (Type I and II nappe groups), which are further divided into six complexes (nappes) each of which is characterized by a rock sequence of Late Paleozoic greenstone/limestone, Permian to Jurassic chert and Jurassic terrigenous clastic rocks. The mode of occurrence of the greenstone is divided into two types. The major basal type occurs as a large coherent slab associated with Permian chert and limestone, constituting the basa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 83 publications
(113 reference statements)
1
18
0
1
Order By: Relevance
“…Bryan & Moore ). Similar chrome spinel has been reported in some late‐Paleozoic greenstones in the Tamba terrane adjoining the Mino terrane (Koizumi & Ishiwatari ), but spinel in most greenstones in the Mino‐Tamba belt is higher in Cr/(Cr+Al) and richer in Fe 3+ and Ti (Agata & Hattori ; Ichiyama et al . ).…”
Section: Occurrence and Chemistry Of Chrome Spinelsupporting
confidence: 79%
“…Bryan & Moore ). Similar chrome spinel has been reported in some late‐Paleozoic greenstones in the Tamba terrane adjoining the Mino terrane (Koizumi & Ishiwatari ), but spinel in most greenstones in the Mino‐Tamba belt is higher in Cr/(Cr+Al) and richer in Fe 3+ and Ti (Agata & Hattori ; Ichiyama et al . ).…”
Section: Occurrence and Chemistry Of Chrome Spinelsupporting
confidence: 79%
“…the crystallization from olivine to clinopyroxene (Ti-augite) plus plagioclase and then amphibole (kaersutite) ( Table 2; Fig. 10A-C; Koizumi and Ishiwatari, 2006;Safonova et al, 2015a), fit the geological and geochemical data. However, the first reported compositions of the Inuyama and Toba samples disagree with the geological and, partly, petrologic data.…”
Section: Tectonic Settings Of Basalts From Accretionary Complexes Of mentioning
confidence: 74%
“…Triangle tectonic discrimination diagrams, MnO-TiO 2 -P 2 O 5 (Mullen, 1983); B, Zr/4-2Nb-Y (Meschede, 1986); C, Zr-Ti/100-3Y (Pearce and Cann, 1973), for basalts from accretionary complexes of Japan (upper row) and for the Archean, Paleozoic and Meso-Cenozoic MORBs (middle row) and OIBs (lower row). The lower two rows show differences between Archean and Phanerozoic MORBs and OIBs and thus imply uncertainties in their application (based on data from Dong et al, 2008;Gordienko et al, 2012;Guo et al, 2007;Ichiyama et al, 2014;Jian et al, 2010;Koizumi and Ishiwatari, 2006;Komiya et al, 2002Komiya et al, , 2004Kuzmichev et al, 2005;Mahoney et al, 2005;Miao et al, 2008;Miyake, 1985;Mizoguchi et al, 2009;Mongush et al, 2011;Regelous et al, 1999;Safonova et al, 2008Safonova et al, , 2009Safonova et al, , 2011aSafonova et al, ,b, 2012Safonova et al, , 2015aTatsumi et al, 1998Tatsumi et al, , 2000Tejada et al, 1996;Ueda and Miyashita, 2005;Volkova and Budanov, 1999;Zhang et al,2009 shown in Suppl. Electr.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Jurassic subduction of the paleo‐Pacific plate beneath the East Asian continent resulted in formation of a several‐thousand kilometers‐long accretionary complex along the continental margin (e.g. Takami & Itaya, 1996; Maruyama et al , 1997; Koizumi & Ishiwatari, 2006). The Jurassic trench, represented by the Tanba–Mino–Ashio Belt (a constituent of the Japanese Jurassic accretionary complex) in Fig.…”
Section: Discussionmentioning
confidence: 99%